Exploring the Relationship between Interest in Higher Education and 12th Grade Mathematics NAEP Scores - Kolhoff, Caitlyn; Zhang, Mingyuan (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2021)
This study presented a secondary analysis of the National Assessment of Educational Progress (NAEP) dataset. The paper examined if a gap exists between the mathematics scores of 12th-grade public school students who have different levels of interest in higher education. - This study used a quantitative descriptive research design to analyze data from the 2013, 2015, and 2019 NAEP data sets. The findings include (1) the average mathematics scale score of students who complete college entrance exams, ACT/SAT, is higher than those who do not complete these exams. (2) The average mathematics scale score of students who complete the FAFSA is higher than those who do not complete the FAFSA. (3) Students who applied to four-year colleges performed significantly higher on the 12th-grade mathematics NAEP than those who did not. (4) Students who applied to two-year colleges performed significantly lower on the 12th-grade mathematics NAEP than those who did not. (5) Students who perceived a future benefit to mathematics scored higher on the mathematics NAEP. These findings indicate that students who are interested in higher education, particularly four-year education, do have higher 12th NAEP mathematics scores. These findings may provide insight into college preparation and guidance at the high school level.